Fe-doped TiO2/Kaolinite as an Antibacterial Photocatalyst under Visible Light Irradiation - Anthoni B. Aritonang; Eka Pratiwi; Warsidah Warsidah; S. I. Nurdiansyah; R. Risko (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2021)
In this work, undoped and Fe-doped TiO2 immobilized on kaolinite surface was successfully synthesized by sol-gel method with various Fe concentrations (0.05, 0.125, and 0.25 wt%). The eﬀects of Fe doping into TiO2 lattice were thoroughly investigated by a diffuse reflectance UV-visible (DRS) spectroscopy, Fourier Transform Infrared (FTIR) spectroscopy, and X-ray diffraction (XRD). The optical band gap of undoped and Fe-doped TiO2/kaolinite is red shifted with respect to the incorporation of Fe3+ into the structure of TiO2 resulted band gap. The FTIR spectra shows a shift of peak at the wave number at 586 cm−1 and 774 cm−1 which is attribute of the Fe−O vibration as an indication of the formation of Fe-TiO2 bonds. Incorporation of Fe3+ cation into the TiO2 lattice replacing the Ti4+ ions, which induced a perturbation in anatase crystal structure, causes the change in the distance spacing of the crystal lattices dhkl(101) of 8.9632 to 7.9413. The enhanced photocatalytic performance was observed for Fe-doped TiO2/kaolinite compared with TiO2/kaolinite with respect to Escherichia coli growth inhibition in solution media under visible light irradiation. Copyright © 2021 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).